The effect of human activity on activity and movement pattern of long-tailed macaques on Big Sister’s island (Pulau Subar Laut) - Gooi, Wen Nee. (2010)
Human-macaque conflicts in Singapore have been on the rise in recent years. It is thus important that we study the macaque population in order to come up with effective management strategies to address the issue. Big Sister’s Island is located south of mainland Singapore and home to some long-tailed macaques. In this study, a population census of the macaques on Big Sister’s Island was done. Following which, individual scan sampling was done to measure the activity budgets of the macaques. Hourly and continuous group location scan samples were taken to determine the times spent by the macaques at different zones furthest from the forests. Macaque movement was compared with human movement pattern to determine if humans affected macaque movement. It was found that there were 19 macaques on Big Sister’s Island. They spent most of their time in the forest, with at least one macaque out in the park more than 70% of the time. In addition, they range more often close to the pier and campsites. Macaques also had a higher tendency to move into areas where campers were on but this was not observed as in the case with workers. Food was the main factor affecting macaque movement.